DEVELOPING MATHEMATICS MODULE WITH REALISTIC MATHEMATICS EDUCATION APPROACH ON THE STATISTIC MATERIAL - Desi Rubiyanti; Suparman Suparman (Universitas Ahmad Dahlan, 2019)
Limitations of teaching materials is a problem that affects the achievement of learning objectives. The existing teaching materials are still challenging to understand. One of the teaching materials that can help students learn actively and independently is the module. This study aims to develop, test the module's feasibility, and determine the student's response to the development of a mathematical module with the RME approach on the subject of statistics. Â The research design used Research and Development with potential and problem steps, data collection, product design, design validation, design revision, product trial, product revision, product trial, and revision trial. Research subjects are material experts, media experts, and student responses in Junior High School (SMP) Negeri 3 Pleret and SMP Muhammadiyah 4 Yogyakarta. This research object is a module of mathematics learning with an RME approach on the Statistic for Students class of SMP in the odd semester. Data collection techniques used questionnaires and interviews. Instrument test through lecturer validation and data analysis using quantitative descriptive analysis. The results showed that the material experts' scores obtained an average score of 83.333 with a good category. The media expert's judgment scored 111.667 with a very good category. The students' responses to the module received a score of 115.842 with the good category. Based on these calculations' results, the mathematics module developed possible use in learning mathematics.